2012
DOI: 10.1063/1.4761984
|View full text |Cite
|
Sign up to set email alerts
|

Optoacoustic measurements of the porosity of paper samples with foxings

Abstract: The goal of this work is to investigate the porosity of old paper with foxings. Initially, paper samples are characterized using the conventional absorption and Fourier transform infrared spectroscopies. Optoacoustic method based on laser excitation of short ultrasound transients is used for porosity measurements. The paper porosity is calculated using the theory of two-component mixture with the experimentally determined sound speeds in paper samples saturated with liquids. An increase in the porosity in foxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…This observation is consistent with what was observed by Balakhnina et al (2012). They consider it, as an oxidation of paper in foxed areas and noted that this oxidation is significantly higher than the general oxidation of paper.…”
Section: Discussionsupporting
confidence: 93%
“…This observation is consistent with what was observed by Balakhnina et al (2012). They consider it, as an oxidation of paper in foxed areas and noted that this oxidation is significantly higher than the general oxidation of paper.…”
Section: Discussionsupporting
confidence: 93%
“…Foxing research from the last six years has undoubtedly linked fungal activity to foxing stains [8][9][10][11][12][13][14][15][16]. Some of these authors [9][10] have also reported a clear increase in porosity and humidity in the interior of the foxing stains.…”
Section: Introductionmentioning
confidence: 99%
“…Foxing research from the last six years has undoubtedly linked fungal activity to foxing stains [8][9][10][11][12][13][14][15][16]. Some of these authors [9][10] have also reported a clear increase in porosity and humidity in the interior of the foxing stains. Sclocchi and co-workers [16], on a study on gelatine-silver foxed photographs, added new insight to the foxing question by documenting a close interaction between the microorganisms and the inorganic materials used in the items' production and proposing that the appearance of the stains depended from the settlement and growth of halotolerant fungi and bacteria that produced localized hot spots of organic material on gelatine.…”
Section: Introductionmentioning
confidence: 99%
“…A laser pulse is absorbed in a layer the thickness of which is determined by radiation wavelength, absorption coefficient of paper and its porosity (scattering coefficient). The porosity can be determined using several methods including optoacoustics [35]. We assume that the scattering coefficient remains unchanged owing to the smallness of ablated mass.…”
Section: Resultsmentioning
confidence: 99%